Mesoscale contribution to the long-range offshore transport of organic carbon from the Canary Upwelling System to the open North Atlantic - Lovecchio, Elisa; id_orcid:0 000-0002-7183-4761; Gruber, Nicolas; id_orcid:0 000-0002-2085-2310; Münnich, Matthias; id_orcid:0 000-0003-3292-2934 (Copernicus, 2018)
ISSN:1726-4170 ISSN:1726-4170